A review of smart electrospun fibers toward textiles. (December 2020) - Liu, Li; Xu, Wenhui; Ding, Yichun; Agarwal, Seema; Greiner, Andreas; Duan, Gaigai
Abstract: Electrospinning as a versatile technology has attracted a large amount of attention in the past few decades due to the facile way to produce micro- and nano-scale fibers featuring flexibility, large specific surface area and high porosity. Stimuli-responsive polymers are a class of smart materials that are capable of sensing surround environment and interacting with them. Therefore, the combination of electrospinning and smart materials could have a great deal of benefits over the development of smart fibers. In this review, it offers a comprehensive understanding of smart electrospun fibers toward textile applications. Firstly, the definition of smart fibers and the differences between interactive fibers and passive interactive fibers are briefly introduced. Then some interactive fibers made from temperature-, pH-, light-, electric field/electricity-, magnetic field-, multi-responsive polymers, as well as some polymers featuring piezoelectric and triboelectric effect which are suitable flexible electrics, are emphasized with their applications in the form of electrospun fibers. Afterwards, some passive and hybrid smart electrospun fibers are introduced. Finally, associated challenges and perspectives are summarized and discussed. Highlights: Understanding of passive smart electrospun fibers and interactive smart electrospun fibers. The recent progress in flexible electronics from electrospun fibers. The recent progress in stimuli-responsive polymers applied in interactive smart electrospun fibers.